(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Implementation of project-based learning in language education is essential to encourage the use and application of real-world languages. It provides students with authentic opportunities to practice language skills in a meaningful context, leading to deeper understanding and retention of language concepts. This article explores the evolution of project-based learning and its potential. benefits for language learners.